2012
DOI: 10.14742/ajet.833
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical knowledge representation through concept mapping as a study and collaboration tool in teacher education

Abstract: This study explored (a) pre-service teachers' perceptions of using concept mapping (CM) in one of their pedagogical courses, (b) the predictive power of such implementation in course achievement, and (c) the role of prior experience with CM, type of mapping, and gender on their perceptions and performances in CM and achievement. The subjects were 89 pre-service teachers majoring in technical education in Turkey. Each participant developed five concept maps and shared them with classmates. The data sources incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
3
15
0
4
Order By: Relevance
“…As well as, the same finding on positive effect of concept mapping on learning was in line with some previous studies such as Van Bon-Martens et al, (2014), Gul and Boman (2006) and Aghakhani et al,(2015), Harrison and Gibbons (2013), and Koc, M. (2012)showed that concept mapping would be effective if appropriately implemented. Therefore, concepts learned via this way can remain for a long-term and increase learning significantly.…”
Section: This Interpretation Was In the Same Line With Zadehsupporting
confidence: 92%
“…As well as, the same finding on positive effect of concept mapping on learning was in line with some previous studies such as Van Bon-Martens et al, (2014), Gul and Boman (2006) and Aghakhani et al,(2015), Harrison and Gibbons (2013), and Koc, M. (2012)showed that concept mapping would be effective if appropriately implemented. Therefore, concepts learned via this way can remain for a long-term and increase learning significantly.…”
Section: This Interpretation Was In the Same Line With Zadehsupporting
confidence: 92%
“…The schematic diagram corresponds to the concepts, propositions, cross-links, and hierarchical relationships of a knowledge framework, so individual concepts as well as their relationships within a specific topic are visualised and presented holistically (Elorriaga et al, 2011;Koc, 2012). In this way, learners are enabled to organise their knowledge and learning experiences, in addition to integrating learning materials (Hwang et al, 2011).…”
Section: Concept Mapmentioning
confidence: 99%
“…Like advance organisers, concept maps are provided for learners as learning scaffolds (Elorriaga et al, 2011;Koc, 2012). Concept maps guide learners to select, organise, and integrate new information during cognitive processing.…”
Section: Concept Mapmentioning
confidence: 99%
“…The concept of competence is connected to a superior performance of a person before a situation, without confusing it with capability or just skill and knowledge, but a sum and integration of both [9]. Competences are repertoire of behaviors that some people master more than others and make them effective in a given situation [8]. A competent person is someone who: (a) possesses certain knowledge, skills and attitudes (KSA) which she or he can use (b) performs specified tasks to (c) a standard of performance expected in (d) a specified workplace under (e) conditions of uncertainty and change [6].…”
Section: Competence: Know Know To Be Know To Domentioning
confidence: 99%